Patient knowledge and attitudes on laser hair removal: A survey in people of color - Vasanop Vachiramon (2018)
Background It is now widely accepted that dark-complexioned skin individuals can be safely treated with laser hair removal (LHR). However, some people are still concerned about the side effects or have been told that hair removal laser is not possible in darkly pigmented skin. Aims To measure the knowledge and attitudes of African Americans about LHR and assess the need for additional education focusing on LHR. Patients/Methods A cross-sectional survey with questionnaire was administered to African American subjects between the ages of 21-70years. Questions comprised attitudes and knowledge about LHR. Demographic characteristics, attitudes, and knowledge were assessed by descriptive statistics. Results were considered statistically significant if P < 0.05. Results The survey was completed by 221 African American subjects. There were only 122 subjects (55.2%) who knew that dark-skinned individuals can be treated with LHR. Only 44.3% of subjects believed that dark-skinned people are more prone to develop hyperpigmentation from LHR. Female subjects and subjects with higher educational background have a higher tendency to consider LHR as a treatment choice (P < 0.05). Conclusions This study shows that many African Americans still have negative attitudes and lack knowledge about LHR. The results of this study provide information that can lead to better informed dermatology providers who can then better educate patients of color regarding LHR knowledge. © 2011 Wiley Periodicals, Inc.